A face in the crowd: imagining individual and collective disabled identities in contemporary China - Dauncey, Sarah (East Asian Studies Center and the Institute for Chinese Studies at The Ohio State University, 2014)
This essay explores the concept of a “disabled crowd” in the Chinese cultural and social imagination. It highlights key terms, analogies, and cultural locations of disability that are seen to relate to and inform group identity and collective behavior, and interrogates these through close readings of a range of contemporary personal narratives and other sources related to the sociopolitical context. It reveals that the appropriation of new and enhanced opportunities for self-representation and self-advocacy is enabling a wide range of disabled people, both on an individual and group level, to “speak out” about their experiences of disability and, just as importantly, “be heard”. What it also shows, however, is that while some disabled people identify with and appear to derive intense personal and social benefit from being associated with a “disabled crowd,” others have used these new opportunities to re-imagine or distance themselves from that same crowd by offering up alternative narratives of what it means to be disabled in China today. In doing so, therefore, the article demonstrates the closely interrelated nature of self and group empowerment and identity in a country where the state has attempted to act as the guardian and voice of disabled people since the 1980s, but where that influence has been increasingly disrupted by voices from across the spectrum of disability.